2020
DOI: 10.1088/1748-9326/abb053
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa agroforestry systems versus monocultures: a multi-dimensional meta-analysis

Abstract: Scientific knowledge, societal debates, and industry commitments around sustainable cocoa are increasing. Cocoa agroforestry systems are supposed to improve the sustainability of cocoa production. However, their combined agronomic, ecological, and socio-economic performance compared to monocultures is still largely unknown. Here we present a meta-analysis of 52 articles that directly compared cocoa agroforestry systems and monocultures. Using an inductive, multi-dimensional approach, we analyzed the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 64 publications
3
78
0
3
Order By: Relevance
“…In addition, the role of baseline choice, for instance, changes compared with potential natural patterns or changes compared with a year in the recent past, should be explored systematically. 142 Furthermore, going beyond investigating the effects of habitat conversion on biodiversity and carbon dynamics will be crucial: land management, for instance, through pesticide 143 and fertilizer use or landscape configuration, 144 has large effects on human health, biodiversity, and aquatic systems, which are presently not sufficiently captured in global models. 145 Lastly, linking the introduction of alien species, which occurs largely through global transport movements, 146 to the trade and consumption of agricultural products will help to draw a more complete picture.…”
Section: Research Frontiersmentioning
confidence: 99%
“…In addition, the role of baseline choice, for instance, changes compared with potential natural patterns or changes compared with a year in the recent past, should be explored systematically. 142 Furthermore, going beyond investigating the effects of habitat conversion on biodiversity and carbon dynamics will be crucial: land management, for instance, through pesticide 143 and fertilizer use or landscape configuration, 144 has large effects on human health, biodiversity, and aquatic systems, which are presently not sufficiently captured in global models. 145 Lastly, linking the introduction of alien species, which occurs largely through global transport movements, 146 to the trade and consumption of agricultural products will help to draw a more complete picture.…”
Section: Research Frontiersmentioning
confidence: 99%
“…Carbon payments are a potential incentive for farmers to plant trees. However, systems directing these payments to cocoa producers are rarely found, and the payments tend to be too low to incentivize the planting of shade trees [13].…”
Section: Agroforestry As a Potential For Climate Change Mitigation And Redd+mentioning
confidence: 99%
“…Hence, the need for an inclusive study that compares the advantages and disadvantages (trade-offs) across the different cocoa production systems [7,8]. Some studies [5,13,14] highlighted some of the trade-offs between agroforestry systems and the intensification practices among cocoa farmers. However, a comprehensive study focusing on the quantification and valuation of these trade-offs could be influential for policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study confirmed that on average, cocoa yields in agroforestry systems are 25% lower than in monocultures, but total system yields are more than 10 times higher, contributing to food security and diversified incomes. In addition, cocoa agroforestry stores 2.5 times more carbon and offer a more stable microclimate, such as lower mean temperature and buffer extremes temperatures (Niether et al, 2020).…”
Section: Introductionmentioning
confidence: 99%